Denosumab Induced Severe Prolonged Hypocalcemia in Metastatic Prostate Cancer - Mehmood, Hassan (J Endocr Soc, 2021)
Background: Denosumab is a RANK-l inhibitor that, in addition to the treatment of osteoporosis, is used in patients with advanced cancer and metastatic bone disease to prevent skeletal-related events. Although denosumab is generally safe and effective, it can cause hypocalcemia which in some patients can be severe and life threatening. We present a case of severe prolonged hypocalcemia after a single dose of denosumab in a patient with metastatic prostate cancer. Case: A 78-year-old male with a past medical history of stage 4 prostate cancer on antiandrogen treatment with GnRH antagonist presented with severe hypocalcemia. Physical exam revealed a blood pressure 125/80 mm Hg, pulse 115 per min and weight 135 lb with negative Chvostek’s and Trousseau’s signs. The electrocardiogram showed supraventricular tachycardia with prolonged QT(c) interval of 503 ms (<430 ms). Labs showed serum calcium 4.9mg/dL (8.5–10.5), albumin 2.5g/dL (3.6–5.1), corrected calcium 5.7 mg/dL, ionized serum calcium 0.64mmol/L (1.05–1.3), creatinine 1.10mg/dL (0.7–1.2), eGFR >60, phosphorus 2.0mg/dL (2.5–4.5), magnesium 1.9 mg/dL (1.6–2.6), 25-OH vitamin D 29.7 ng/mL (30–100), 1,25 dihydroxy vitamin D 174 pg/mL (18–64), iPTH 244.0 pg/mL (11–68) and PSA 1860 ng/mL. Three weeks prior to presentation, the patient received 120 mg of subcutaneous denosumab. Pre-treatment serum calcium was 9.2 mg/dL (8.5–10.5), and Tc-99m bone scan showed multiple osteoblastic osseous metastatic lesions involving both axial and appendicular skeleton. The patient was diagnosed with denosumab-induced severe hypocalcemia and started on intravenous (IV) calcium gluconate infusion, oral phosphate 250 mg twice daily, and ergocalciferol 50,000 IU twice weekly. He required IV calcium gluconate up to 10 g per day in addition to oral calcium carbonate 2 g t.i.d. for 2 weeks to resolve hypocalcemia and normalize QT(c) interval. Patient was discharged to nursing home on calcium carbonate 2 g q.i.d. with IV calcium gluconate as needed to keep corrected calcium >8.0 mg/dL. After discharge he required up to 4 g of IV calcium and 8 g of oral calcium per day. Unfortunately, he presented again with severe hypocalcemia 5 weeks after discharge. In addition to current regimen of oral and IV calcium boluses, low dose calcitriol was started. We were only able to maintain his serum calcium>8.0 mg/dL by administering high daily dose of oral calcium carbonate 8 g /day and calcitriol 2 mcg daily. Due to poor prognosis, he was transitioned to hospice care and died 2 weeks later. Discussion: There are not many case reports on severe prolonged hypocalcemia secondary to denosumab in cancer patients but normal kidney function. Our patient remained on high dose of calcium even 101 days after denosumab administration. Reference: 1. Milat F et al. Prolonged hypocalcemia following denosumab therapy in metastatic hormone refractory prostate cancer. Bone. 2013 Aug 1;55(2):305–8.